The welfare cost of external habits: a quantitat ive assessment - Gómez, Manuel A. (Estudios de Economía, 2016)
This paper quantifies the welfare cost of consumption externalities in an endogenous growth model with habit formation. Agent's utility depends on both current consumption and a reference consumption level determined by economy-wide average past consumption. Although utility may be lower in the presence of consumption externalities, the welfare loss relative to the efficient growth path is found to be very small. This result is extremely robust to variations in the parameter values. However, there are relatively important differences in the timing of the welfare loss and in generational welfare.